Redox activity of iron diazine-diimine carbonyl and dinitrogen complexes: a comparative study of the influence of the heterocyclic ring - Doll, Julianna S.; Regenauer, Nicolas I.; Bothe, Viktoria P.; Wadepohl, Hubert; Roşca, Dragoş-Adrian (Inorganic chemistry, 2022)
A detailed investigation of the electronic structure of diazinediimine iron complexes and their comparison with the pyridine analogues reveals subtle but important differences, imparted by the supporting heterocycle. In the case of LFe(CO)2 complexes (L = pyrazine- and pyrimidinediimine), the characterization of three available redox states confirmed that whereas the nature of the electron-transfer processes is similar, the differences in π-acidity of the supporting heterocycle significantly affect the redox potentials. The reduction of LFe(CO)2 can yield either a ligand-centered radical (for L = pyrimidine) or a C-C-bonded dimer (for L = pyrazine), supported by a dearomatized core. In the latter case, the C-C bond can be reversibly cleaved oxidatively. Compared to the carbonyl analogues, employing weak-field N2 ligands triggers changes in electronic structure for the neutral and reduced LFe(N2) complexes (L = pyrimidinediimine). En route to the synthesis of the nitrogen complexes, the square-planar LFeCl (L = pyrimidinediimine) was isolated. The monoradical character of the supporting chelate triggers the asymmetric distribution of electron density around the heterocycle.
Published: December 16, 2021
Gesehen am 22.03.2022